2020
DOI: 10.1021/acscatal.0c02146
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the ZrO2–Pd Interface for Selective CO2Hydrogenation by Overcoating an Atomically Dispersed Pd Precatalyst

Abstract: Tailoring the interfacial sites between metals and metal oxides can be an essential tool in designing heterogeneous catalysts. These interfacial sites play a vital role in many renewable applications, for instance, catalytic CO2 reduction. Postsynthesis deposition of metal oxide on supported metal catalysts can not only create such interfacial sites but also prevent particle sintering at high temperature. Here, we report a sol–gel-based strategy to synthesize an atomically dispersed “precatalyst”. In contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 67 publications
2
13
0
1
Order By: Relevance
“…All the corresponding Ru/oxide catalysts produced predominantly methane as product ( Fig. 5 H ), in agreement with previous reports ( 24 , 30 , 32 , 34 , 50 ), with Ru/ZrO 2 being the only exception and showing prominent RWGS selectivity of 78% possibly due to either strong metal support interactions ( 51 ) or Ru redispersion ( 52 ). Nevertheless, in all cases it was found that IPOP encapsulation significantly promoted CO production through RWGS pathway and, more importantly, much increased C 2+ hydrocarbon selectivity.…”
Section: Resultssupporting
confidence: 91%
“…All the corresponding Ru/oxide catalysts produced predominantly methane as product ( Fig. 5 H ), in agreement with previous reports ( 24 , 30 , 32 , 34 , 50 ), with Ru/ZrO 2 being the only exception and showing prominent RWGS selectivity of 78% possibly due to either strong metal support interactions ( 51 ) or Ru redispersion ( 52 ). Nevertheless, in all cases it was found that IPOP encapsulation significantly promoted CO production through RWGS pathway and, more importantly, much increased C 2+ hydrocarbon selectivity.…”
Section: Resultssupporting
confidence: 91%
“…From previous findings, the metal site in cooperation with the oxygen vacancy site of ZrO 2 was responsible for the adsorption and activation of oxygenated molecules. 36,61,62 According to XPS (Tables S5 and S6) and OSC results, Co/ZR3 exhibited the highest concentration of oxygen vacancies on the catalyst surface, which seemed to verify the fact that the presence of oxygen vacancy on the ZrO 2 support contributed to substrate activation.…”
Section: Methodsmentioning
confidence: 83%
“…For example, in a Ru/CeO 2 single-atom catalyst, CO was stabilized at the interface and methane was produced by its successive hydrogenation . Therefore, along with the isolation of metal atom sites, it is important to understand the role of interfacial site to control the activity and selectivity of catalysts. …”
Section: Introductionmentioning
confidence: 99%